Crossing : from Middelheim museum to the city and back again. - Tentoonstelling. Antwerpen. Middelheimmuseum; Boomgaard, Jeroen; Lindmayr, Ulrike; Matthe, Jan; Meewis, Menno (Gent : CAHF, 2011)
Jeroen Boomgaard [...] offers a theoretical reflection on [art in the public space]. [...] fifteen visual artists were asked to formulate an answer to this question: "Which sculpture from the museum would you bring to the Middelheim Museum and [...] which sculpture from the museum had better move to the city?
12.03.2011 - 23.04.2011
boek